THE RESEARCH OF TECHNOLOGICAL PROPERTIES OF SEA BUCKTHORN MEAL - Ekaterina Olegovna Nikulina; Olga Yakovlevna Kolman; Galina Valentinovna Ivanova (Современная наука и инновации, 2022)
The results of researches of technological properties of the fat-free sea buckthorn meal are presented in the article. Processes of swelling capacity at various temperature - time parameters of the water environment, antioxidant activity and influence on physical properties of a gluten and baking properties of wheat flour were studied.